Multifactorial challenges in cardiometabolic disease management: patient, healthcare system, and environmental barriers - Ambari, Ade Meidian (Universitas Brawijaya, 2024)
Cardiometabolic disease is a complicated issue characterized by various contributing factors. The patients typically have multiple comorbidities with mostly modifiable risk factors. Regarding cardiovascular risk factors, patients' long-term dedication, bad diets, sedentary lifestyles, and psychological problems should be closely monitored. In addition to the patient's internal characteristics, environmental factors such as air pollution have also been linked to cardiovascular-related morbidity and death. Improved public health policy and therapeutic resource fulfillment are crucial to reducing the disease burden and ensuring better patient outcomes. The Government should improve the system and encourage the implementation of guidelines-based cardiovascular disease management.